O Reuni como política pública de expansão da educação superior na perspectiva de estudantes universitários do Câmpus Palmas-UFT - Lopes, Odiberto de Souza (Universidade Federal do Tocantins, 2016)
This study has as general objective verifying the execution process of the Reuni Program and its interdisciplinary proposals from the students’ perspectives of the courses Reuni Campus Palmas / UFT. The conceptual basis used is historical-critical matrix. Supported in psychosocial theoretical concepts, the research aimed to understand the subjective process of contemporary youth facing the consumer society and the reflexes of the divestment of young students from the academic culture. In this logic, it was realized a qualitative research with six college students from Reuni Courses from the Universidade Federal do Tocantins, Palmas Campus. The subject analysis accomplished pointed to the following results: i) There is a crisis legitimacy from the university related to its social function and the ideals weakening that had as source, locus of culture and knowledge; ii) The subjectivity processes of contemporary youth facing the somatic culture and consumer society demonstrated concernment in the divestment of studies and the utilitarian adherence in education; iii) The interdisciplinary proposals predicted in Reuni pedagogical guidelines demonstrated, with the individuals interviewed a non-achievement of their goals, in particular by educational and methodological difficulties from the faculty members. Finally, suggestions were elaborated for the Reuni courses coordinators containing action proposals targeting assistance on the process of adaptation and retention of young scholars in the university environment